Nurses' experiences of compassion when giving palliative care at home. (February 2020) - Devik, Siri Andreassen; Enmarker, Ingela; Hellzen, Ove
Background: Compassion is seen as a core professional value in nursing and as essential in the effort of relieving suffering and promoting well-being in palliative care patients. Despite the advances in modern healthcare systems, there is a growing clinical and scientific concern that the value of compassion in palliative care is being less emphasised. Objective: This study aimed to explore nurses' experiences of compassion when caring for palliative patients in home nursing care. Design and participants: A secondary qualitative analysis inspired by hermeneutic circling was performed on narrative interviews with 10 registered nurses recruited from municipal home nursing care facilities in Mid-Norway. Ethical considerations: The Norwegian Social Science Data Services granted permission for the study (No. 34299) and the re-use of the data. Findings: The compassionate experience was illuminated by one overarching theme: valuing caring interactions as positive, negative or neutral, which entailed three themes: (1) perceiving the patient's plea, (2) interpreting feelings and (3) reasoning about accountability and action, with subsequent subthemes. Discussion: In contrast to most studies on compassion, our results highlight that a lack of compassion entails experiences of both negative and neutral content. Conclusion: The phenomenon of neutral caring interactions and lack of compassion demands further explorations from both a patient – and a nurse perspective.